Increasing access to and uptake of livestock vaccines and women's empowerment with gender-responsive vaccine delivery systems - Galiè, Alessandra; Njiru, Nelly; Omondi, Immaculate A.; Malapit, Hazel J.; Ferguson, Nathaniel; Lecoutere, Els; Muchiri, Caroline (CGIAR GENDER Impact Platform, 2025)
There are persistent and significant gender gaps in low- and middle-income countries (LMICs) which negatively impact productivity, food security and livelihoods. Livestock, particularly chickens, sheep and goats, are essential to sustain livelihoods and nutrition in rural areas of LMICs. They are particularly important to the livelihoods of women and their households given that women farmers in rural areas have few alternative ways of making a living. Preventable, deadly diseases such as Newcastle (ND) and Peste des petits ruminants (PPR), however, often decimate flocks of chicken and herds of sheep and goats. Vaccines to prevent these diseases exist, yet livestock keepers, particularly women in rural areas, infrequently use them. Without these interventions, the health and productivity of the animals are compromised and so is women’s ability to support their livelihoods and that of their households. Both technological and social factors limit access to and uptake of livestock vaccines. For example, technological factors may include a lack of cold chain infrastructure to transport the livestock vaccines. Socio-institutional factors may include informal rules in a community that forbid women from liaising with unrelated men, reducing their ability to obtain animal health services and vaccines from vets (who are almost exclusively men). The empowerment of women is often seen as a way of addressing gender-based disadvantage and providing women with the capabilities to leverage livestock to support their livelihoods and that of their families. Empowered women farmers are more likely to hear about, access, adopt, utilize and benefit from animal vaccines and healthier livestock. Facilitating women’s empowerment requires addressing women’s limited agency, access to resources, and opportunities. These in turn are influenced by restrictive gender norms, that shape informal rules of behavior and inequitable policies. Gender-responsive policy efforts bundled with interventions that transform restrictive norms could potentially support women’s engagement in the livestock sector and their potential to get empowered.